ANALYSIS OF THE EFFECTIVENESS OF SUPPLIER SELECTION THAT AFFECT TO BUSINESS’ PRODUCTIVITY (CASE STUDY: AYAM GORENG NELONGSO) - Novia Ika Triyono; Rizal Mahleffi (AIBPM Publisher, 2018)
The purpose of this journal is to identify the effectiveness of the supply chain from the point of supplier selection. This study is important because some businesses in Indonesia are not interest how to choose and determine the quantity of suppliers that can support the productivity of the company. This study uses Ayam Goreng Nelongso as a case study. Data analysis that obtained as the basic of writing this journal is through interviews with related parties. The theory that applied in this journal are based on the material that has been submitted by the author's lecturer to find the best strategy for choosing supplier. Keywords: Supplier Selection, Business’ Productivity, Ayam Goreng Nelongso.